Sustainable Synthesis of Pure Silica Zeolites from a Combined Strategy of Zeolite Seeding and Alcohol Filling - Wu, Qinming; Zhu, Longfeng; Chu, Yueying; Liu, Xiaolong; Zhang, Changsheng; Zhang, Juan; Xu, Hao; Xu, Jun; Deng, Feng; Feng, Zhaochi; Meng, Xiangju; Xiao, Feng‐Shou (Angewandte Chemie International Edition, 2019)
Currently, the synthesis of pure silica zeolites always requires the presence of organic structure‐directing agents (OSDAs), which direct the assembly pathway and ultimately fill the pore space. A sustainable route is now reported for synthesizing pure silica zeolites in the absence of OSDAs from a combined strategy of zeolite seeding and alcohol filling, where the zeolite seeds direct crystallization of zeolite crystals from amorphous silica, while the alcohol is served as pore filling in the zeolites. Very importantly, the alcohol could be fully washed out from zeolite pores by water at room temperature, which completely avoids calcination at high temperature for removal of OSDAs in the synthesis of pure silica zeolites. A sustainable route for synthesizing pure silica zeolites in the absence of organic structure‐directing agents from a combined strategy of zeolite seeding and alcohol filling is presented. The zeolite seeds direct crystallization of zeolite crystals from amorphous silica, while the alcohol is served as pore filling in the zeolite.